The Gaia view of the Cepheus OB2 association. Issue 1 (9th January 2023) - Szilágyi, Máté; Kun, Mária; Ábrahám, Péter; Marton, Gábor
ABSTRACT: OB associations, birthplaces of the most luminous stars, are key objects for understanding the formation of high-mass stars and their effects on their environments. The aim of this work is to explore the structure and kinematics of the Cepheus OB2 association and characterize the history of star formation in the region – in particular, the role of the Cepheus Bubble, surrounding Cepheus OB2. Based on Gaia DR3 data, we study the spatial and age distribution and kinematics of young stars in the region. We select candidate pre-main-sequence stars in the M G versus G BP − G RP colour–magnitude diagram, and using a clustering algorithm, we identify 13 stellar groups belonging to Cep OB2. Four groups, consisting of 10–13 Myr old low- and intermediate-mass stars, are located in the interior of the bubble and are part of the oldest subsystem of the association Cep OB2a. Younger groups are found on the periphery. The tangential velocities suggest that some groups on the periphery were born in an expanding system of star-forming clouds, whereas others have been formed due to the collision of their parent cloud with the expanding bubble.